Tecnologia para produção de banana-passa da cv. Thap maeo produzida no Amazonas - Santos, Natasha Veruska Carvalho dos (Instituto Nacional de Pesquisas da Amazônia - INPA, 2008)
The cultivate Thap maeo, developed by Embrapa, distributed by the Institute of Agricultural Development of the State of Amazon, now it is produced and marketed in natura. Resistant to diseases and with technological qualities, the lack acceptance of the fruit in natura and of processing technology it is still an impediment for the culture of banana in Amazon. As the development of technologies for conservation and aggregation of value is a strategy for APL's in Amazon, it was had as objective evaluates methods of prevention of the enzymatic darkening and of dehydration for banana-raisin obtaining starting from the cv. Thap maeo. Ripe fruits given in by Embrapa-CPAA were washed,sanitizados (NaClO 0,01%), submitted to Blanching treatments (water to 94 °C for two minutes) and immersion in Na2Cl2O5 ofsodium to 0,01% and acid solution (0,25% of ascorbic acid and 0,30% of citric), and preceded or not of osmotic dehydration for immersion during six hours in sucrose solution to 65 ºBrix, they were dry in dryer (with circulation of air) to 65 ºC. The obtained products were appraised as the chemical composition, texture, activity of water and coloration. Ally to the treatments of prevention of the darkening, the osmotic dehydration contributed to the quality,providing the banana-raisin of the cv. Thap maeo better appearance, coloration, texture and characteristics physiochemical, smaller activity of water, larger income and smaller production cost. The banana-raisin production appears as strategy for conservation and aggregation of value for the cv. Thap maeo, serving as base for the local productive Arrangements - APL's in Amazon. Key words: darkening prevention, osmotic dehydration, chemical composition, texture and coloration, production cost.
Keywords: prevenção de escurecimento da banana; Desidratação osmótica da banana; Composição química da banana; textura e coloração da banana; Banana-passa